2020
DOI: 10.3390/jcm9103315
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Viral Load, IFNλ Polymorphisms and the Course of COVID-19: An Observational Study

Abstract: The course of SARS-CoV-2 infection ranges from asymptomatic to a multiorgan disease. In this observational study, we investigated SARS-CoV-2 infected subjects with defined outcomes, evaluating the relationship between viral load and single nucleotide polymorphisms of genes codifying for IFNλs (interferon). The study enrolled 381 patients with laboratory-confirmed SARS-CoV-2 infection. For each patient, a standardized form was filled including sociodemographic variables and clinical outcomes. The host’s gene po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
(27 reference statements)
4
30
0
1
Order By: Relevance
“…This observation may help to understand the disproportionate prevalence of COVID-19 in the black population with a lower frequency of the protective CC allele than in the white population (6,9). The fact that there were no significant differences in CC expression between non-severe and severe disease proposes a role for IFNL4 in early stages, but not in disease progression as previously suggested (10).…”
Section: Discussionsupporting
confidence: 55%
“…This observation may help to understand the disproportionate prevalence of COVID-19 in the black population with a lower frequency of the protective CC allele than in the white population (6,9). The fact that there were no significant differences in CC expression between non-severe and severe disease proposes a role for IFNL4 in early stages, but not in disease progression as previously suggested (10).…”
Section: Discussionsupporting
confidence: 55%
“…Amodio et al . demonstrated that the median PCR Ct was significantly lower in patients who died or needed critical care than in those who were hospitalized and discharged alive, or exclusively attended at home, but after adjusting for age and sex, there was not and independent association with critical care need or death 13 .…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have reported that a high number of virus copies in NP swabs, mainly defined as a cycle threshold (Ct) < 25 or < 22 in the real-time polymerase chain reaction (RT-PCR), was an independent risk factor for intubation and/or death 8 11 . However, other studies have not found independent association between low Ct values and critical care admission or death 12 , 13 . In short, the real impact of initial SARS-CoV-2 viral load in NP swabs on COVID-19 patients’ outcomes is not been fully elucidated, and this issue remains controversial 14 .…”
Section: Introductionmentioning
confidence: 85%
“…2020 [ 118 ] CCR5 3p21.31 Chemokine receptor CCR5 Δ32 Increased susceptibility to SARS-CoV-2 infection and mortality Panda. 2020 [ 74 ] IFNL4 19q13.2 Immune response to viral infection rs368234815TT/∆G Higher viral loads Amodio et al 2020 [ 79 ] Other genes DBP 4q11–q13 Regulator of total and free vitamin D metabolite levels rs7041 GT and TT genotype are positively and negatively related to the rate of SARS-CoV-2 infection and mortality, respectively Karcioglu et al 2020 [ 141 ] DPP4 2q24.2. Serine exopeptidase rs13015258 Expression of key regulatory genes related to internalization of SARS-CoV-2 into the cell Senapati et al 2020 [ 62 ] VKORC1 16p11.2 Decreased vitamin K level 1639A (rs9923231) Associated with protection against thrombotic complications of COVID-19 Janssen et al 2020 [ 217 ] …”
Section: Angiotensin-converting Enzyme 1 and Angiotensin-converting Enzyme 2 Polymorphismsmentioning
confidence: 99%
“…IFNL4 is located on chromosome 19q13.2 and is involved in the defense against viral infections, such as HCV, RSV and influenza virus [ 78 ]. Amodio et al reported that polymorphisms at the rs368234815TT/∆G locus of the IFNL4 gene are associated with a higher SARS-CoV-2 viral load [ 79 ].…”
Section: Immune System Gene Polymorphismmentioning
confidence: 99%